2009
DOI: 10.1002/hed.21037
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell adhesion molecule expression: No correlation with perineural invasion in cutaneous squamous cell carcinoma of the head and neck

Abstract: N-CAM expression did not predict neurotropism in our patient population. Additional studies are required to identify the cell surface markers expressed by CSCCHN which confer neurotropism capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Vural et al [28] concluded that there is significant increase of NCAM with PNI. In 2009, Solares et al [29] contradicted the earlier hypothesis.…”
Section: Discussionmentioning
confidence: 37%
“…Vural et al [28] concluded that there is significant increase of NCAM with PNI. In 2009, Solares et al [29] contradicted the earlier hypothesis.…”
Section: Discussionmentioning
confidence: 37%
“…Select studies on SCC of the H&N (McLaughlin et al, 1999;Vural, Hutcheson, Korourian, Kechelava, & Hanna, 2000), pancreatic cancers (Aloysius et al, 2010), and adenoid cystic carcinoma (Gandour-Edwards, Kapadia, Barnes, Donald, & Janecka, 1997) have found associations between NCAM and PNI. In contrast, there are at least two other studies in pancreatic cancers and SCCs of the H&N which have failed to demonstrate such an association (Kameda et al, 1999;Solares, Brown, Boyle, Parsons, & Panizza, 2009). …”
Section: Other Potential Players: Ncam and Cxcr4mentioning
confidence: 74%
“…In 2000, Vural et al [16] evaluated surgical specimens of 66 patients using monoclonal IgG antibody immuno peroxidase staining for NCAM and concluded that there was significant increase in the expression of NCAM in patients with PNI than in patients without PNI. In 2009, Solares et al [17] reported that there was no expression of NCAM in all of the 18 patients with head and neck cutaneous SCC (including 14 patients with clinical PNI and 4 control patients without PNI). Previous theories proposing a mechanism of spread along lowresistance planes and endoneural lymphatic channels have now largely been discounted.…”
Section: Pathogenesismentioning
confidence: 99%